Effectivity of Green Open Spaces as Bird Habitats in Bogor City and Its Surroundings - Sry Wahyuni; . Syartinilia; Yeni Aryati Mulyani (http://arl.faperta.ipb.ac.id/, 2018)
Green open spaces can be potential habitats for birds in urban landscapes. Due to high number of land development, the green open spaces in urban landscapes tend to be small and scattered. Indeed, analysis about effectivity of green open spaces as bird habitats in Bogor City and its surroundings is needed. We investigated bird habitat patches on 14 locations in Bogor City and its surroundings. This study aimed to analyze the effectiveness of bird habitat patches for bird species richness using two variables (size and complexity). The data were analyzed using the Pearson Correlation and multiple linear regression. The results showed that there were no significant differences between bird species richness and size of patches. Conversely, there were significant differences between bird species richness and complexity of patches. The Pearson Correlation revealed that there were high correlation between bird species richness and complexity of patches. Finally, we propose three recommendations of green open spaces as bird habitat patches in Bogor City and its surroundings, such as protecting and managing both small and large bird habitat patches, increasing number of vegetation strata and number of vegetation in some strata in small bird habitat patches, and increasing number of vegetation in some strata in large bird habitat patch with low bird speciess richness.